Thermal analysis of the heat exchanger used in a regenerative Brayton cycle under real working conditions (2019)
The quality of the energy transformation processes focuses on improving the energy efficiency of the components used in a thermodynamic cycle with the aim to upgrade the application of the resources needed to produce energy in power generation plants. Due to the great importance of thermal analysis in the kinetic energy transformation of a fluid into electrical energy through combined Rankie cycles applied on industrial processes, this paper proposes an energetic and exergetic analysis of a heat exchanger used as a steam surface condenser with the aim to reduce the fuel consumption used by a steam turbine and to establish parameters that define the performance of the shell and tube heat exchanger using computational tools of thermal analysis. An experimental model has been used to validate the numerical analysis developed in a virtual environment. MATLAB software has been used as a numerical tool to develop the matrix manipulations written in .m code that define the thermal analysis of the equations that describe the behavior of the combined regenerative Rankine cycle power plant. Numerical data generated in the numerical model with MATLAB has been compared with the experimental model of the steam surface condenser. A good agreement has been reached between the CFD analysis and the experimental model of the steam surface condenser.